IMPROVING STUDENTS’ SPEAKING ABILITY BY USING INSTRUCTIONAL MEDIA FOR ADVANCED LEARNERS - Fitrawati, Fitrawati (English Department FBS UNP, 2015)
Nowadays, the use of media in language learning is very important. It will make the teaching and learning process be more attractive and effective. Instructional media is an aid which is able to help teacher in their teaching activity. There are many kinds of media that can be used in teaching and learning process, especially in teaching speaking. This article will discuss the use of video as one of instructional medias to teach speaking for advanced learners. A video can be used for presenting the content, starting conversation and providing illustration for concept. By applying the steps of using video in teaching speaking, hopefully, teachers can take benefit from it. There are three steps of using video in speaking activities; namely: choosing the video, preparing the viewing guide and speaking task.Key word: instructional media, video, teaching speaking